Early detection of rotor-bar faults of three-phase induction motor using motor current signature analysis method - . Syafrudin; Arnawan Hasibuan (Syiah Kuala University, 2011)
Three-phase induction motors play a pivotal role in industry and there is a strong demand for their reliable and safe operation. They are generally reliable but eventually do wear out. Faults and failures of induction motor can lead to excessive downtimes and generate large losses in terms of maintenance and lost revenues, and this motivates the examination of on-line condition early detecting. On-line condition early detecting involves taking measurements on a motor while it is operating in order to detect faults with the aim of reducing both unexpected failures and maintenance costs. Motor Current Signature Analysis (MCSA) method is a way to detection of condition monitoring technique used to early detection problems in rotor bar fault of three- phase induction motors. In this paper presented the experimental results of frequency spectrum Fast Fourier Transform (FFT) stator current on-line censorship a three-phase induction motor using LabVIEW algorithm for detecting of rotor conductors faults. The stator current FFT analyzed using Motor Current Signature Analysis (MCSA) method.